Sistem Pengendalian Persediaan Bahan Baku dengan Metode Economic Order Quantity pada PT Kayu Lapis Indonesia di Kaliwungu - Auliya Ma’rifatul Jannah; Sukemi Kamto Sudibyo (Jurnal Manajemen Informatika & Teknologi, 2026)
The central aims of diagnosing pressing difficulties and gauging the advantageous repercussions of a sistem for raw material inventory control were addressed in a study published in 2026, identified as "Raw Material Inventory Control Sistem Using the Economic Order Quantity Method at PT Kayu Lapis Indonesia in Kaliwungu." This particular research adopted a descriptive quantitative approach, dedicating its efforts to the measurement and computational aspects of inventory asset values. The collection of data for this research involved conducting direct physical inventory counts at the company's premises during the period spanning April, May, and June in the year 2025. Upon completion of the data acquisition process, the Economic Order Quantity (EOQ) framework was strategically applied to sistematically process and analyze the inventory figures that had been gathered. The resultant analytical findings emphatically demonstrated a considerable aggregate reduction in the overall expenses pertaining to raw material inventory for the manufacturing of plywood, amounting to Rp. 3,021,065,598. This considerable abatement equates to an improvement of 84.68%, particularly when evaluated against the established requisite quantity of 1,397,569 units of raw materials.